Bioactive components and clinical potential of Astragalus species - Li, Shuo; Hu, Xunpeng; Liu, Fen; Hu, Weiming (Frontiers in Pharmacology, 2025)
Astragalus L., the world’s largest vascular plant genus, has been used medicinally and as food for centuries, especially in traditional Chinese medicine It is widely applied in immune modulation, antioxidant therapy, anti-inflammatory treatments, and antitumor applications. Recent studies show that Astragalus species is rich in bioactive compounds, such as polysaccharides, flavonoids, saponins, alkaloids, and simple phenolics, which demonstrate significant pharmacological effects, including anti-inflammatory, antioxidant, immunomodulatory, and antitumor properties, along with potential benefits for Alzheimer’s disease and diabetes. This review synthesizes 140 references to analyze 51 newly identified flavonoids, 31 triterpenoid saponins, and 19 alkaloids in Astragalus (2020–2025), focusing on their chemical structures and bioactivities. It also examines Astragalus species in medicine and food homology (MFH) and how processing methods affect its efficacy. Furthermore, the mechanisms behind its anti-inflammatory, antioxidant, immune-boosting, antitumor, neuroprotective, and hypoglycemic effects are discussed. Future studies should prioritize large-scale clinical trials to confirm Astragalus’s efficacy and safety, explore combination therapies, and improve sustainable resource utilization to expand its medical and food applications. Keywords: Bioactive molecules, Astragalus, Pharmacological action, Mechanism of action, Medicine and food homology (MFH).